Securing Fragile Democracies in the Balkans: the European Dimension - Geoffrey Pridham (Romanian Journal of European Affairs, 2008)
The European Union faces unprecedented difficulties in its integration of the Western Balkans in terms of the requirements for change by countries in that region wishing to join. In order to meet this challenge, the EU’s political conditionality has moved significantly beyond its demands made on the post-Communist entrants of 2004 and 2007. But its effort to bridge the gap between the ability or political will of Balkan countries to adapt to European modernisation and uncertainties about EU commitment created by “enlargement fatigue” among Member States is vulnerable to weak consensus on both sides. Accordingly, the dynamic behind further enlargement is not comparable with the historic drive that impelled the enlargement of 2004. At the same time, there are strong geopolitical arguments on grounds of stabilising the Balkans for going ahead with integrating the Western half of this region.